Do apostates represent a hidden population of abuse victims? - Parekh, Hari (2016)
Apostates are individuals raised within religious families, having identified as religious yet, currently disbelieve in the existence of God, or Gods, with a lack of belief in religion, and currently identify as non-religious. Given the strong feelings families can have about the rejection of their faith, this study sought to examine how abusive this could be for the apostate, expecting that apostates represent hidden population of abuse victims within religious households. 228 persons (102 Male: 119 Female) were recruited from an online survey with the support of Faith to Faithless and were screened using the modified conflict tactics scale to quantify experience of assault, serious assault, psychological abuse and negotiation.